Business cycles - Central Bank of Nigeria, Research Department (Abuja, Nigeria Central Bank of Nigeria., 2016)
Discusses the definitions, concept, phases of business cycle, leading indicators, theories, causes and global and domestics trends in business cycles
Includes bibliographical references.
oif 01/06/17
Ref.
Keywords: Business cycles -- Economic aspects